Protective effect of chelerythrine on gentamicin-induced nephrotoxicity - Parlakpinar, H; Tasdemir, S; Polat, A; Bay-Karabulut, A; Vardi, N; Ucar, M; Acet, A (Wiley, 2006)
Despite their beneficial effects, aminoglycosides including gentamicin (GEN) have considerable nephrotoxic side-effects. The toxicity of GEN at the level of the kidney seems to relate to the generation of reactive oxygen species (ROS). ROS have been reported to be involved in the activation of protein kinase C (PKC). The unique structural aspects of PKC cause it to function as a sensor for oxidative stress. It seems likely that the increased NAD(P)H oxidase-derived superoxide (O-2) production is at least in part mediated by PKC. We investigated the effects of chelerythrine, a commonly used PKC inhibitor, on GEN-induced changes of renal malondialdehyde (MDA), nitric oxide (NO) generation, catalase (CAT), superoxide disniutase (SOD), glutathione peroxidase (GSH-Px) activities, glutathione (GSH) content, and serum creatinine (Cr), blood urea nitrogen (BUN) levels. Morphological changes in the kidney were also examined. GEN administration to control rats increased MDA and NO generation but decreased CAT, SOD and GSH-Px activities, and GSH content. Chelerythrine administration with GEN caused significantly decreased MDA, NO generation and increased CAT, SOD and GSH-Px activities, and GSH content when compared with GEN alone. Chelerythrine also significantly decreased serum Cr and BUN levels. Morphological changes in the kidney including tubular necrosis were evaluated qualitatively. Both biochemical findings and histopathological evidence showed that administration of chelerythrine reduced the GEN-induced kidney damage. We propose that chelerythrine acts in the kidney as a potent scavenger of free radicals to prevent the toxic effects of GEN via the inhibition of a PKC pathway. Copyright (c) 2004 John Wiley & Sons, Ltd.
Keywords: gentamicin; chelerythrine; nephrotoxicity; protein kinase C; reactive oxygen radicals; rat